Three Phase Load Flow Investigations in the Context of Smart Grid - Ashfaq, S.; Malik, T. N. (The Nucleus, 2014)
The developments & progress in communications, information and control have revolutionized the conventional grid. Currently integration of renewable energy resources, dynamic optimization techniques, advanced performance analysis tools, monitoring and measurements are handled under the smart grid umbrella. Central and distributed generation control requires efficient load flow analysis and monitoring at both levels. Three phase load flow investigations have been carried out on three real time systems: National Transmission and Dispatch Company (NTDC), 32-Bus 500/220 kV primary Power System, the distribution systems of Islamabad Electric Supply Company (IESCO) 11 kV, 81-nodes and University of Engineering & Technology (UET), Taxila 21-nodes by simulating in MATLAB Simulink Environment. Smart Environment has been created in three systems with increasing complexity from system 1 to system 3 and system 3 is proposed Smart Grid Model for UET Taxila. NTDC primary network has been analyzed with the integration of Renewable Energy Resources (RERs), Static Var Compensators (SVC) and IESCO distribution network subject to RERs, Distribution Static Compensation (D-STATCOM) with monitoring of parameters at control Centre in both cases. System 3 is simulated with Solar Integration, D-STATCOM, Electric Fuel Cell Vehicle (FCV), Intelligent Distribution Boards (DBs), and monitoring through Transmission Communication Protocol over Internet Protocol (TCP/IP) in control Centre. Idea of smart DBs is proposed and implemented for load management. The simulation results of three-phase Load Flow Analysis successfully proved its potential strength for smart environment.